Analisis Nilai Budaya dalam Promosi Wisata Akun Instagram @Wonderfulindonesia dan @Japantravelcom - Mafiroh, Kholifatul; Wibowo, Kunto Adi (JURNAL LENSA MUTIARA KOMUNIKASI, 2022)
The lack of cultural analysis research on tourism based Instagram accounts, especially in Indonesia, makes it a limitation in understanding communication studies, especially cross cultural in Indonesia. This study aims to look at the differences in cultural values resulting from cultural based Instagram account postings and tourism promotions @Wonderfulindonesia and @Japantravelcom which are based on two components of Hofstede’s cultural theory which include collectivist-individualist cultural values and power distance (PD) as well as cultural dimensions in the image. mise en scene. Quantitative content analysis method was used to analyze 400 samples tested through Pearson chi square and continuity correction chi square. The results showed that the two Instagram accounts showed more individualism than collectivists in posting pictures. In the post caption, @Wonderfulindonesia shows the individualist side as opposed to @Japantravelcom. The results of the analysis of Power distance and mise en scene do not show a significant difference between Instagram account of @Wonderfulindonesia and @Japantravelcom.